An improved LC–MS/MS method for determination of cinacalcet in human plasma and its application to the evaluation of food intake effect on the pharmacokinetics of cinacalcet in healthy volunteers. (5th August 2019) - Li, Lin‐ling; Chen, Cai‐li; Cai, Ning‐fang; Yi, Jin‐ling; Zheng, Chao; Feng, Yan; Xiong, Wen‐gang; Luo, Xi; Li, Wei‐hua; Cheng, Ze‐neng
Abstract: A liquid chromatography–tandem mass spectrometry (LC–MS/MS) method for the determination of cinacalcet in human plasma was developed and validated. This assay was based on liquid–liquid extraction and cinacalcet‐d4 was used as an internal standard (IS). Separation was achieved on a C18 column by the mobile phase A of water (containing 0.1% formic acid) and the mobile phase B of acetonitrile–water (95:5, v/v) (containing 0.2% formic acid) with gradient elution. Quantification was done using multiple reaction monitoring mode to monitor the precursor‐to‐product ion transitions of m / z 358.2 → m / z 155.2 for cinacalcet and m / z 362.3 → m / z 155.0 for IS at positive ionization mode. The calibration curve was established over the range 0.05–20.0 ng/mL and the correlation coefficient was >0.99. The intra‐ and inter‐day relative standard deviations were <5.8%. Accuracy determined at four concentrations ranged between 96.0 and 106.0%. This method was successfully applied to a pharmacokinetic description of oral dose of cinacalcet and the significant effect of food intake on the pharmacokinetics of cinacalcet was first demonstrated in Chinese healthy volunteers.